Problems and Challenges of Islamic Education Today and Their Solutions in the Global Era - Safira, Alya; Nursanti, Desi; Fadhilah, Aiman Maulida; Azis, Abdul (Synergy: Journal of Collaborative Sciences, 2025)
Islamic education currently faces complex challenges that are not only administrative and infrastructural, but also touch on substantial aspects such as curriculum relevance, teaching quality, and character building. This study aims to analyze these problems and future challenges with a qualitative approach through literature studies from various scientific literature sources. The results of the analysis show that the problems of Islamic education include weak educational paradigms, lack of teacher professionalism, conservative learning methods, and minimal research enthusiasm. On the other hand, upcoming challenges such as value crises, pragmatism, and the negative influence of technology need to be anticipated with an integrated strategy. Suggested efforts include developing a relevant curriculum, improving teacher quality, expanding access to education, and integrating religious knowledge with science. In conclusion, Islamic education needs to be adaptive and solution-oriented to produce a generation that is knowledgeable, faithful, and has noble character. It is recommended that all stakeholders play an active role in the reform of Islamic education in order to answer global challenges contextually and sustainably.